The Influence of Education and Attitude of Pregnant Women on Antenatal Care Visits at Health Centers - Qudratullah, Fyzria; Pudyastuti, Rita Retna; Rahmat, Rezqiqah Aulia; Subani, Natalia Debi; Herlina, Herlina (International Journal of Health Sciences, 2025)
Antenatal care (ANC) visits are one of the important efforts in reducing maternal and infant mortality rates. However, compliance of pregnant women in conducting ANC visits is still a challenge in various regions. This study aims to determine the effect of education level and attitudes of pregnant women on the frequency of ANC visits at the Community Health Center. This study used a quantitative design with a cross-sectional approach. The sample of the study was 100 pregnant women who visited Community Health Center X during the last six months. Data were analyzed using the chi-square test and logistic regression. The results showed that education level (p = 0.003) and attitudes of pregnant women (p = 0.001) had a significant effect on compliance with ANC visits. It can be concluded that the higher the education and positive attitudes of pregnant women, the higher the likelihood of them making ANC visits according to standards. Therefore, interventions in the form of health education and counseling are needed to increase awareness of pregnant women regarding the importance of ANC.